THINK PAIR SHARE (TPS) TECHNIQUE FOR IMPROVING STUDENTS READING COMPREHENSION OF NARATIVE TEXT IN THE SEVENTH GRADE STUDENTS OF SMPN 3 KLARI KARAWANG - Anisa Yulianti; Hesti Arum Lestari; Yana Yana (PROJECT (Professional Journal of English Education), 2019)
This research used Classroom Action Research. Think Pair Share can be trusted to help students comprehend reading skill. The population of the research were the students of SMPN 3 Klari Karawang in Academic years 2017-2018. The total population of the students in this academic year are 280 students. The number of sample were 30 students. The data was gathered from the test and observation. After being implementated of Think Pair Share activities in every cycle, the students’ reading score were getting better. We can see from the result of students’ average score Cycle I 63.47 and Cycle II 79.67. In conclusion, the Technique of Think Pair Share can improve learners’ reading comprehension.